Involvement of prenucleation clusters in calcium phosphate mineralization of collagen. (15th January 2021) - Ma, Yu-xuan; Hoff, Samuel Edmund; Huang, Xue-qing; Liu, Juan; Wan, Qian-qian; Song, Qun; Gu, Jun-ting; Heinz, Hendrik; Tay, Franklin R.; Niu, Li-na
Abstract: Involvement of thermodynamically-stable prenucleation clusters (PNCs) in the biomineralization of collagen has been speculated since their existence was reported in mineralization systems. It has been hypothesized that intrafibrillar mineralization proceeds via nucleation of inhibitor-stabilized intermediates produced by liquid-liquid separation ( aka. polymer-induced liquid precursors; PILPs). Here, the contribution of PNCs and PILPs to calcium phosphate intrafibrillar mineralization of collagen was examined in a model with a semipermeable membrane that excludes nucleation inhibitor-stabilized PILPs from reaching the collagen fibrils, using cryogenic electron microscopy of reconstituted fibrils and conventional transmission electron microscopy of collagen sponges. Molecular dynamics simulation with the Interface force field (IFF) was used to confirm the existence of PILPs with amorphous calcium phosphate and elucidate details of the dynamics. Furthermore, intrafibrillar mineralization of single collagen fibrils was experimentally observed with unstabilized PNCs when anionic/cationic polyelectrolytes were used to establish Donnan equilibrium across the semipermeable membrane. Molecular dynamics simulation verified PNC formation within the collagen intrafibrillar gap zones at the atomic scale and explained the role of external PILPs. The PILPs decrease the interfibrillar water content and increase the interfibrillar ionic concentration. Nevertheless, intrafibrillar mineralization of collagen sponges with PNCs alone was inefficacious, being constrained by competition from extrafibrillar mineral precipitation. Statement of Significance: Compared with conventional PILP-based intrafibrillar mineralization, mineralization of collagen fibrils using unstabilized PNCs is constrained by competition from extrafibrillar mineral deposition. The narrow window of opportunity for PNCs to produce intrafibrillar mineralization provides a plausible explanation for the feasibility of nucleation inhibitor-free intrafibrillar apatite assembly during reconstitution of type I collagen. Graphical abstract: Image, graphical abstract